2010
DOI: 10.1007/s10545-010-9128-0
|View full text |Cite
|
Sign up to set email alerts
|

Folate and cancer: how DNA damage, repair and methylation impact on colon carcinogenesis

Abstract: Inappropriate diet may contribute to one third of cancer deaths. Folates, a group of water-soluble B vitamins present in high concentrations in green, leafy vegetables, maintain DNA stability through their ability to donate one-carbon units for cellular metabolism. Folate deficiency has been implicated in the development of several cancers, including cancer of the colorectum, breast, ovary, pancreas, brain, lung and cervix. Generally, data from the majority of human studies suggest that people who habitually c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
194
0
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 237 publications
(204 citation statements)
references
References 78 publications
(103 reference statements)
2
194
0
8
Order By: Relevance
“…5 There is consensus in the literature indicating that individuals who habitually consume the greatest quantities of folate, or who have the highest concentrations of blood folate, are at decreased risk for the development of CRC. 6,7 However, folate derivatives are cofactors in nucleotide synthesis and high levels of the vitamin could therefore promote the proliferation of rapidly dividing cells. 6,7 Indeed, the current opinion is that higher folate intake is protective against CRC development in nearly all circumstances except for those individuals who consume an excessive amount of the vitamin and have existing neoplastic lesions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 There is consensus in the literature indicating that individuals who habitually consume the greatest quantities of folate, or who have the highest concentrations of blood folate, are at decreased risk for the development of CRC. 6,7 However, folate derivatives are cofactors in nucleotide synthesis and high levels of the vitamin could therefore promote the proliferation of rapidly dividing cells. 6,7 Indeed, the current opinion is that higher folate intake is protective against CRC development in nearly all circumstances except for those individuals who consume an excessive amount of the vitamin and have existing neoplastic lesions.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 However, folate derivatives are cofactors in nucleotide synthesis and high levels of the vitamin could therefore promote the proliferation of rapidly dividing cells. 6,7 Indeed, the current opinion is that higher folate intake is protective against CRC development in nearly all circumstances except for those individuals who consume an excessive amount of the vitamin and have existing neoplastic lesions. 6,7 Given its pivotal role in DNA methylation processes, onecarbon metabolism has been largely investigated as a potential modulator of DNA methylation in CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Folate, a water-soluble B vitamin, including endogenous food folate and its synthetic form, folic acid (FA), is a necessary micronutrient for normal human growth and development (6,7). Early in 1965, Hibbard et al (8) reported the association between apparent folate defi ciency and neural tube birth defect (NTD).…”
mentioning
confidence: 99%
“…Severe and prolonged folate depletion in rodents induces global DNA hypomethylation in the liver and certain regions of the colon (49)(50)(51) ). Moderate folate deficiency does not consistently induce global DNA hypomethylation in blood, liver and colon, despite a significant depletion in blood and tissue folate and liver SAM (52)(53)(54) . Lymphocyte DNA is hypomethylated in women made experimentally folate deficient over several weeks (55,56) and low-dietary folate intake (< 200 mg/d) correlates with hypomethylation of long-interspersed nucleotide element repeats (LINE-1; used as an indicator of global DNA methylation) in human colon tumours (57) .…”
Section: Folate Deficiency Cancer and Cvd: A Common Mechanismmentioning
confidence: 92%